Patterns of Identity: Textiles in Aotearoa: http://www.textiles.org.nz - Fraser, Angela (Auckland University of Technology, 2004)
Patterns of Identity: Textiles in Aotearoa (POI) is an online information resource documenting New Zealand textiles. First published in 1999 as a Web site, the POI resource was expanded in 2001 to include a textile image database. POI has been developed as a resource for textile design education, textile practitioners, cultural tourists and textile enthusiasts. It provides a showcase for contemporary New Zealand textiles and focuses on printed textiles with examples of local cultural influences. The resource is accumulative and forms an archive of textile practice presented through an extensive online image collection. This exegesis provides a background to these aspects of the project and discusses issues associated with the building of the POI as an online resource. It discusses the collation, design and evaluation of this project as well as considering the scope for future development.
Keywords: Textile crafts -- New Zealand; Textile fabrics -- New Zealand; Web sites -- Design